2015
DOI: 10.1186/s40064-015-0889-7
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and associated factors of axillary web syndrome in women who had undergone breast cancer surgery: a transversal and retrospective study

Abstract: BackgroundBreast cancer is the most common malignancy among women. Surgical treatment is an essential part of therapy, which still includes chemotherapy, radiotherapy and hormone therapy. The increase in early cancer detection and less aggressive treatment has made longer survival rates possible for women with this neoplasia. Morbidities after treatment have subsequently aroused particular interest in the scientific community in order to minimize their effects and provide increased quality-of-life for these pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 18 publications
1
19
0
2
Order By: Relevance
“…A third but smaller (n = 36) prospective cohort study showed a significant relationship between lower BMI and AWS in univariate analysis [6]. In contrast, a retrospective, descriptive design showed no significant association between AWS and BMI although the women with AWS had a lower mean BMI than those without (27.29 vs. 28.15); the authors commented that their failure to find a difference may have been due to the fact that the vast majority of women in their sample were overweight or obese [10].…”
Section: Risk Factors For Developing Axillary Web Syndromementioning
confidence: 63%
See 2 more Smart Citations
“…A third but smaller (n = 36) prospective cohort study showed a significant relationship between lower BMI and AWS in univariate analysis [6]. In contrast, a retrospective, descriptive design showed no significant association between AWS and BMI although the women with AWS had a lower mean BMI than those without (27.29 vs. 28.15); the authors commented that their failure to find a difference may have been due to the fact that the vast majority of women in their sample were overweight or obese [10].…”
Section: Risk Factors For Developing Axillary Web Syndromementioning
confidence: 63%
“…Younger age has been shown also to be a risk factor for developing AWS (or cording) in 4 prospective cohort studies [6][7][8]10]. In that younger women with breast cancer typically have a lower BMI, it has been speculated that age and BMI are related in their risk contributions [7].…”
Section: Risk Factors For Developing Axillary Web Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found an association between vigorous PA performance and risk of developing AWS. The authors who previously examined risk factors for developing AWS found no relationship between training level and increased risk of AWS 47 , 48 , with the exception of a case report that described AWS development after physical effort 49 . Moreover, among the risk factors for the development of AWS should be considered younger age, greater time elapsed since surgery and number of resected lymph nodes 50 , but PA was not considered.…”
Section: Discussionmentioning
confidence: 97%
“…Currently in Italy over 37,000 new cases are diagnosed per year (1), (2) 25% of which women below 50 years of age (3). Axillary surgical procedures have reported, along with post-operative morbidity of bleeding, infections, presence of lymphedema and shoulder pain, also the axillary fibrous banding syndrome, better known as axillary web syndrome (AWS), that normally appears between the first and the fifth week after surgery (5),(6) diagnosed on 28.86% of women (7), (8), its manifestation is mainly at the level of ipsilateral axillary region at surgical dissection, but it can also extend towards the elbow, throughout the antecubital space and, in the most serious cases, up to the column of the thumb ( 9),(10), causing upper limb functional deficits (11). The purpose of the description of this clinical case is to create an appropriate physiotherapic protocol to deal with patients having AWS in a rehabilitation ser-vice, through an active and passive manual therapy of the upper limb and cervico-dorsal segment (MAP) together with self-mobilization exercises to do at home (EA), both established the MAPEA protocol.…”
Section: Introductionmentioning
confidence: 99%